Synergistic Apoptotic Effect Of Indole-3-Carbinol And Doxorubicin On Pre-B Acute Lymphoblastic Leukemia Cells - Behnaz Tavasoli; Majid Safa; Ahmad Kazemi (Tehran University of Medical Sciences, 2015)
Background and Aim: Indole-3-carbinol (I3C), found in Brassica species vegetables, exhibits antitumor effects. It has been shown that I3C induces apoptosis in various cell types through inactivation of the nuclear factor-kappa B (NF- k B) pathway. Anthracyclines such as doxorubicin, is widely used in the treatment of hematological malignancies, induce apoptosis in tumor cells via DNA damage and activation of p53. However, NF- k B pathway that activated by anthracyclines as a part of DNA damage response can induce chemo resistance. In this study the apoptotic effect of doxorubicin in combination with NF- k B inhibitor I3C was assessed in acute lymphoblastic leukemia cells. Materials and Methods: Human pre-B acute lymphoblastic leukemia cell line, NALM-6 cells, were preincubated with various concentrations of I3C for1 hour and then treated with 125nM doxorubicin at 37 ° C for 24 hours. Cellular DNA content assay and Annexin V-FITC staining were performed by flowcytometry for evaluation of apoptosis. Results: DNA histogram analysis of NALM-6 cells indicates that combination of I3C with doxorubicin synergistically escalated the percentages of sub-G1 population cells (apoptotic cells) as compared to doxorubicin-only treated group. Annexin V-FITC staining showed that cotreatment of NALM-6 cells with I3C and doxorubicin increased the proportion of Annexin-V positive cells (early apoptotic cells) in comparison with the doxorubicin treated cells. Conclusion: The results of cell culture treatments and cell death analysis by flowcytometry suggest that I3C synergistically potentiates doxorubicin-induced apoptosis in human leukemia NALM-6 cells.